Habituating STEM Integration Through Learning Communities: a Development Study in Banjarmasin, Indonesia - Winarti, Atiek; Yulinda, Ratna; Khairunnisa, Yasmine; Kaspul, Kaspul; Tong, Tan Lik (Indonesian Journal on Learning and Advanced Education (IJOLAE), 2026)
STEM education trains students to solve complex problems by integrating knowledge of science, techno-logy, engineering, and mathematics into a learning experience. While awareness of STEM's importance is growing among educators in Indonesia, consistent integration into Science \instruction remains challenging. This development study investigates the effectiveness of a STEM-Learning Community (STEM-LC) model in habituating STEM practices among Indonesian science teachers. Utilizing the Plomp development model, the study involved ten schools across two implementation cycles. The STEM-LC model comprised five structured phases: (1) forming a learning community, (2) learning about STEM, (3) preparing lesson plans, (4) conducting learning phases one and two, and (5) reflection. The model's practicality was assessed based on the execution and fluidity of each stage, teachers' responses to the STEM-LC model, their understanding of STEM, and students' feedback on STEM learning. Data were collected through observation sheets and questionnaires, then analyzed qualitatively and descriptively. Findings revealed that the STEM-LC habitua-tion model was implemented effectively, achieving a score of 91, with the 'social system' aspect rated highest. Notably, 96.6% of teachers successfully implemented STEM learning, and students responded positively, scoring 72.5. Students expressed enjoyment in STEM activities and a desire for continued enga-gement. Despite initial unfamiliarity with STEM, the structured phases of the STEM-LC facilitated more straightforward implementation. These results demonstrate that the STEM-LC model is a viable and effecti-ve strategy for developing sustained STEM integration habits in Science education and holds potential for broader implementation across Indonesian schools.